1992
DOI: 10.3382/ps.0711043
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Balance and Urinary and Fecal Mineral Excretion Profile of Broilers Housed in Thermoneutral and Heat-Distressed Environments

Abstract: Two experiments were conducted utilizing 4- to 7-wk posthatching Vantress x Arbor Acres male broilers to evaluate heat distress effects on mineral balance partitioned into urinary and fecal loss. In the first study, 8 colostomized and 14 intact birds were allotted to two environmental chambers maintained at either a thermoneutral temperature (24 C) or a cycling temperature heat distress (24 to 35 C) in a switch-back design. Birds were precision-fed 2% of body weight thrice daily to equalize consumption prior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 17 publications
0
17
0
1
Order By: Relevance
“…Vitamin D is involved in Ca and P absorption in the gut, bone formation and bone demineralisation and Ca and P resorption by the kidney (Combs, 1998;Atencio et al, 2006). The negative effect of heat stress on mineral excretion has been noted in previous reports (Smith and Teeter, 1987;Belay et al, 1992;Sahin et al, 2006b). Studies have shown that high ambient temperature influences retention and excretion of minerals in poultry (Smith and Teeter 1987;Sahin et al, 2006b).…”
Section: Discussionmentioning
confidence: 89%
“…Vitamin D is involved in Ca and P absorption in the gut, bone formation and bone demineralisation and Ca and P resorption by the kidney (Combs, 1998;Atencio et al, 2006). The negative effect of heat stress on mineral excretion has been noted in previous reports (Smith and Teeter, 1987;Belay et al, 1992;Sahin et al, 2006b). Studies have shown that high ambient temperature influences retention and excretion of minerals in poultry (Smith and Teeter 1987;Sahin et al, 2006b).…”
Section: Discussionmentioning
confidence: 89%
“…Birds subjected to a heat stress environment reduced phosphorus absorption (El-Husseiny and Creger, 1981) and retention (Belay et al, 1992). Moreover, under unfavorable rearing conditions at high temperatures, the phosphorus requirement may be altered (Persia et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, from the study described herein, it appears that environmental temperature influences the nutrient content of some parts. Increased mineral excretion (Belay et at, 1992) and decreased feed intake (Smith and Teeter, 1993) are two consequences of heat stress. These factors may have an impact on the distribution of nutrients in the broiler carcass.…”
Section: Resultsmentioning
confidence: 99%
“…They include changes in respiration rate (Linsley and Burger, 1964), acid-base balance (Teeter and Smith, 1986), mineral balance (Smith and Teeter, 1987), and feed consumption (Smith and Teeter, 1993). Research (Belay et al, 1992) has shown that heat stress has an adverse effect on mineral balance with increased excretion of several minerals. The physiological changes that result from heat exposure may have an effect on the deposition of nutrients in different tissues.…”
Section: Introductionmentioning
confidence: 98%